A Human Rights-Based Approach to Foreign Agricultural Investment in Uganda. Issue 2 (May 2019) - Ashukem, Jean-Claude N.
Abstract : The use of human rights approaches in the context of development-related activities appears to be the most appropriate means to observe respect for and the protection of people's rights as states are required to adhere to human rights norms and standards. This article argues for the adoption of a rights-based approach within the framework of foreign agricultural investment activities in Uganda in order to ensure respect for, the protection of and the fulfilment of the fundamental human rights of local communities. It provides an exposition of the procedural and substantive rights which are contained in the relevant international and regional legal instruments and which need to be taken into account in such a rights-based approach. It also distils the relevant benchmarks to be used by the government of Uganda as the standards to be achieved in order to ensure the observance and protection of people's rights, especially with regard to the negotiation and implementation of foreign agricultural investment land deals in Uganda. It then compares the Ugandan legal framework against the distilled benchmarks to ascertain if and to what extent the legal framework conforms to these requirements with regard to regulating foreign agricultural investment activities. Based on the distilled minimum human rights requirements and the obligation they bestow on states, the article concludes that in order for the government of Uganda to properly and effectively respect, protect and fulfil local communities' human rights, it is crucially important that it should consider these requirements and fulfil them during the regulation and implementation of foreign agricultural investment land deals in the country.